The Celebrity Factory: New Modes of Fashion Entrepreneurship - Marta Martina; Silvia Vacirca (ZoneModa Journal, 2017)
The aim of the paper is to analyze the contribution of celebrity culture to the re-shaping of the fashion industry, distancing from an oppositional view while embracing a systemic one, where celebrity is considered a fundamental engine of the contemporary cultural production of fashion and a global consumerist culture. The scope of our paper tries to overcome the endorsement point of view to address the relationship between celebrity and fashion as a two-way relationship which is re-wiring the fashion industry. The paper will explore the multiple manifestations of the so-called celebrity brand labels, from Kim Kardashian to Victoria Beckham.